2022
DOI: 10.3390/cells11192971
|View full text |Cite
|
Sign up to set email alerts
|

Regulation Networks of Non-Coding RNA-Associated ceRNAs in Cisplatin-Induced Acute Kidney Injury

Abstract: Cisplatin is widely used as a chemotherapeutic drug to treat various solid tumors. However, it often induces severe side effects, including nephrotoxicity, which limits its application in clinical settings. Furthermore, the underlying mechanisms of action are unclear. Here, we applied whole-transcriptome RNA sequencing to a cisplatin-induced acute kidney injury (CP-AKI) mouse model to evaluate competing endogenous RNA (ceRNA) networks. We found 4460 mRNAs, 1851 long non-coding RNAs, 101 circular RNAs, and 102 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
0
0
Order By: Relevance
“…38 It is proposed that in AKI, Plk1 inactivates NOTCH1 as it acts as a substrate for hairy/ enhancer-of-split related with YRPW motif 1 and hairy and enhancer of Split 1 (HEY1/HES1), which are NOTCH targets and are associated with Plk1-linked DNA deterioration, resulting in cellular necrosis. 39 Furthermore, NOTCH signaling acts in two phases; the first is the reduced NOTCH1 expression, and the second phase entails developing resistance to the downregulation of NOTCH1. The continued expression of NOTCH1 helps to maintain metabolic activities that enhance the protection of cells against oxidative stress (Figure 3).…”
Section: Plk1 In Akimentioning
confidence: 99%
See 1 more Smart Citation
“…38 It is proposed that in AKI, Plk1 inactivates NOTCH1 as it acts as a substrate for hairy/ enhancer-of-split related with YRPW motif 1 and hairy and enhancer of Split 1 (HEY1/HES1), which are NOTCH targets and are associated with Plk1-linked DNA deterioration, resulting in cellular necrosis. 39 Furthermore, NOTCH signaling acts in two phases; the first is the reduced NOTCH1 expression, and the second phase entails developing resistance to the downregulation of NOTCH1. The continued expression of NOTCH1 helps to maintain metabolic activities that enhance the protection of cells against oxidative stress (Figure 3).…”
Section: Plk1 In Akimentioning
confidence: 99%
“…A study has revealed that in the cisplatin‐induced AKI rats, Plk1 overexpression, along with other cyclin‐dependent protein kinases, correlated with DNA damage 38 . It is proposed that in AKI, Plk1 inactivates NOTCH1 as it acts as a substrate for hairy/enhancer‐of‐split related with YRPW motif 1 and hairy and enhancer of Split 1 (HEY1/HES1), which are NOTCH targets and are associated with Plk1‐linked DNA deterioration, resulting in cellular necrosis 39 . Furthermore, NOTCH signaling acts in two phases; the first is the reduced NOTCH1 expression, and the second phase entails developing resistance to the downregulation of NOTCH1.…”
Section: The Crucial Nexus Of Plk1 In the Development And Progression...mentioning
confidence: 99%
“…FOXM1 plays a role in renal tubule repair after acute renal injury. The transcription factor FOXM1 regulates gene expression levels in the AKI model [91]. The expression of FOXM1 increased after renal ischemia-reperfusion in mice.…”
Section: Foxm1 and Acute Kidney Injurymentioning
confidence: 99%